2017
DOI: 10.1021/jacs.7b01593
|View full text |Cite
|
Sign up to set email alerts
|

Energy Storage during Compression of Metal–Organic Frameworks

Abstract: Practical applications of metal-organic framework (MOF) materials require an in-depth understanding of their mechanical properties. We have investigated the mechanical properties and energy absorption behavior of single crystals of four isostructural UiO-type MOFs under uniaxial compression. In situ nanocompression experiments were used to measure the mechanical behavior of individual MOF nanocrystals under compression within a transmission electron microscope. The plasticity and endothermicity during deformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 35 publications
2
51
0
Order By: Relevance
“…60 Suslick also conducted experiments to determine the energy storage of UiO-66 upon compression, revealing that MOFs may have potential applications as mechanical shock absorbers or dissipators. 61 Experimental evidence of the impact of defects on the compression of UiO-66 was reported by Dissegna et al, corroborating Coudert's ndings that increasing defect density generally yields a lower bulk modulus. 62 By conducting these experiments in a water-lled cell rather than a traditional DAC, the pressure control at low pressures is exceptionally precise, allowing for measurements in 25 MPa intervals from 0-4 GPa.…”
Section: Uio-66supporting
confidence: 53%
“…60 Suslick also conducted experiments to determine the energy storage of UiO-66 upon compression, revealing that MOFs may have potential applications as mechanical shock absorbers or dissipators. 61 Experimental evidence of the impact of defects on the compression of UiO-66 was reported by Dissegna et al, corroborating Coudert's ndings that increasing defect density generally yields a lower bulk modulus. 62 By conducting these experiments in a water-lled cell rather than a traditional DAC, the pressure control at low pressures is exceptionally precise, allowing for measurements in 25 MPa intervals from 0-4 GPa.…”
Section: Uio-66supporting
confidence: 53%
“…The promising device performances of ZIF‐8 and CuBTC MOFs during bending tests hint that their elasticity may make them suitable for flexible electronics, which is attractive given the growing demand for small and robust sensors for applications such as distributed sensor networks and wearable technologies. We are also intrigued by recent prospects of MOFs for shock absorption and dissipation applications, including an exciting recent study that showed the per gram energy absorption for UiO‐type MOFs at compressive stresses greater than 2 GPa is similar to the amount of energy that is released in the explosion of trinitrotoluene (TNT) …”
Section: Discussionmentioning
confidence: 99%
“…Cav-1, the major structural protein of caveolae, functions as scaffolding protein [21] regulating multiple physiological processes including caveola biogenesis, vesicular transport, cholesterol homeostasis, and signal transduction [22]. Recently, Cav-1 has been demonstrated to be closely involved in tumorigenesis and development, affecting the proliferation [23, 24], survival [25, 26], apoptosis [27, 28], migration [29, 30], invasion [24, 31], metastasis [32, 33], autophagy [34, 35], transformation [36], anoikis [37, 38], and chemotherapy resistance [39, 40] processes of cancer cells. Cav-1 is generally regarded as a tumor suppressor, and studies have implicated loss of Cav-1 in the pathogenesis and progression of multiple human cancers [4144].…”
Section: Introductionmentioning
confidence: 99%